(untitled) (Perspectiva Pictorum, 2024)
Resumo: Este trabalho apresenta a peculiaridade da representação das sibilas na arte colonial de Diamantina, Minas Gerais. Sendo as únicas representações das profetisas na colônia, elas estão contornadas por estruturas de falsa arquitetura inspiradas em Andrea Pozzo e apresentam uma centralidade incomum e única no mundo. Segundo Joyce Lussu toda a cultura hegemônica teve que prestar contas à sibila, manipulá-la e deformá-la e ainda assim não a conseguiu suprimir. Nestas representações tão características, reafirma-se a dimensão multicultural do mito feminino que faz o elo entre o divino e o humano, com importância confirmada pelas suas dimensões e centralidade, além da sofisticação das estruturas de quadratura. Palavras chave: Sibilas, centralidade feminina, profetisas. Abstract: Abstract: This paper introduces the peculiarity of the representation of the sibyls in the colonial art of Diamantina, Minas Gerais. As the only representations of the prophetesses in the former Portuguese colony, they are surrounded by structures of false architecture inspired by Andrea Pozzo and present a centrality that is unusual and unique to sybil representations worldwide. According to Joyce Lussu, all hegemonic cultures had to account for the sibyls, to manipulate and deform their image and reputation - and, even so, none was not able to suppress them. In these very characteristic representations, the multicultural dimension of this feminine myth which makes the link between the divine and the human, is reaffirmed and its importance is confirmed by its dimensions and centrality, as well as by the sophistication of the square structures surrounding them. Key words: Sibyls, feminine centrality, prophetesses.